IL 6 levels in Periodontitis Induced Rabbits after Treatment with Neem Bark Extract - Gul e Nazish, Rai Sadaf Nawaz, Ayesha Shmakh, Arshadullah Afridi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: IL-6 has crucial role in the response to microbial insults. It acts as pro-inflammatory and anti-inflammatory agent. Hence IL 6 is an important inflammatory marker of periodontal disease. Levels of IL6 in Gingival crevicular fluid strongly indicate presence of periodontal disease which ultimately results in many health hazards. Aims: To measure levels of IL 6 in periodontitis induced rabbits after treating animals with neem bark extract and amoxicillin at doses of 500mg/kg and 20mg/kg and to see anti-inflammatory effects of neem bark extract. Methods: Forty eight white New Zealand rabbits were divided in four groups A, B, C and D. Group A was healthy control. Group B was disease group. Group C was neem treated. Group D was amoxicillin treated. Periodontitis was induced and rabbits were given treatment with neem bark extract and amoxicillin for 10 days. Samples were obtained with the help of periopaper absorbent strip and marginal auricular vein and analyzed in laboratory. ELISA test was performed to find levels of IL 6 in all four groups. Practical implication: To gain the evidence that neem can be used in maintenance of oral hygiene and prevention of oral diseases. Results: Treatment with neem bark extract and amoxicillin equally reduced IL 6 levels among group c and D after treatment (0.033±0.003) in gingival crevicular fluid when compared with diseased group B (0.089±0.007).P value was less than 0.001. Conclusion: Neem bark extract has significant effects on reduction of IL 6 levels in gingival crevicular fluid of periodontitis induced rabbits Neem bark extract possess anti-inflammatory and anti-microbial action. Keywords: IL6, Periodontitis, GCF, Inflammation, Neem